2021
DOI: 10.1097/mou.0000000000000958
|View full text |Cite
|
Sign up to set email alerts
|

Technical advances in nerve-sparing and continence preservation

Abstract: Purpose of reviewUrinary incontinence and erectile dysfunction are common after radical prostatectomy. These side effects greatly impact patients' quality of life. Therefore, surgical techniques and technology tools are constantly being developed to optimize trifecta outcomes. Here we focus on advances in nerve-sparing (NS) and continence preservation. Recent findingsNew surgical techniques dedicated to preservation rather than reconstruction have been developed to improve urinary continence (UC) and NS. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In their study, the authors noted that at 1 year after surgery, potency rates varied from 54% to 63%. Erectile function after RP has been closely associated with the quality of nerve sparing (NS) [5][6][7][8]. While some have attributed variations in outcomes to the surgeon's skill or the way potency and continence are measured, research has shown that the extent of neural preservation and the use of an atraumatic and traction-free dissection can significantly improve functional results [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the authors noted that at 1 year after surgery, potency rates varied from 54% to 63%. Erectile function after RP has been closely associated with the quality of nerve sparing (NS) [5][6][7][8]. While some have attributed variations in outcomes to the surgeon's skill or the way potency and continence are measured, research has shown that the extent of neural preservation and the use of an atraumatic and traction-free dissection can significantly improve functional results [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, results were limited, as the accuracy of prediction was only about 70% 7 . Recent studies suggest that the preservation of periprostatic structures by intraoperative surgical techniques such as nerve‐sparing (NS), bladder neck‐preserving, and Retzius‐sparing modalities are associated with early recovery from UI after RARP 8–10 . Although surgical procedures can be expected to improve early recovery from UI, it is difficult to objectively assess the relationship between surgical procedures and the preservation of anatomic structures and whether they contribute to early recovery from UI after RARP.…”
Section: Introductionmentioning
confidence: 99%